Briligence

Unlock the full course today
Get full access to all videos, exercise files.
Kumar Rohan

Physics and Mathematics

Save
Please login to bookmark Close

Uniform Acceleration

An object is said to be moving with a uniform acceleration if its velocity changes by equal amounts in equal intervals of time.

Formulae for uniformly accelerated motion along a straight line

Consider an object, moving with a uniform acceleration ‘a‘ along a straight line OX, with origin at O. Let the object reach at points A and B at instants $ \displaystyle {{t}_{1}}\text{ and }{{t}_{2}}$. Let $ \displaystyle {{x}_{1}}\text{ and }{{x}_{2}}$ be the displacements of the object at time $  \displaystyle {{t}_{1}}\text{ and }{{t}_{2}}$ respectively and $ \displaystyle {{v}_{1}}\text{ and }{{v}_{2}}$ be the velocity of the object at position A and B respectively.

 

Acceleration

 

(i) Velocity-time relation

$  \displaystyle \because \text{acceleration }=\dfrac{{\text{change of velocity}}}{{\text{time taken}}}$

$ \displaystyle \begin{array}{l}\therefore a=\dfrac{{{{v}_{2}}-{{v}_{1}}}}{{{{t}_{2}}-{{t}_{1}}}}\text{ }…\text{(1)}\\\Rightarrow {{v}_{2}}-{{v}_{1}}=a\left( {{{t}_{2}}-{{t}_{1}}} \right)\\\Rightarrow {{v}_{2}}={{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)\text{ }…\text{(2)}\end{array}$

Let origin of time axis be taken at A and $ \displaystyle u$ be the velocity of the object at A and $  \displaystyle v$ be velocity of the object at B after time t. Then

$ \displaystyle \begin{array}{l}{{v}_{1}}=u;{{t}_{1}}=0;{{v}_{2}}=v\\\text{and }{{t}_{2}}=t\end{array}$

Putting values in (2), we get

$  \displaystyle v=u+at$

The relations (2) and (3) are required velocity-time relations.

(ii) Position-time relation

Let $ \displaystyle {{v}_{{av}}}$ be the average velocity of the object during the motion of the object from A to B,

$ \displaystyle {{v}_{{av}}}=\dfrac{{\text{total displacement}}}{{\text{total time taken}}}=\dfrac{{{{x}_{2}}-{{x}_{1}}}}{{{{t}_{2}}-{{t}_{1}}}}$

$ \displaystyle \begin{array}{l}\text{or }{{x}_{2}}-{{x}_{1}}={{v}_{{av}}}\left( {{{t}_{2}}-{{t}_{1}}} \right)\\\text{But, }{{v}_{{av}}}=\dfrac{{\text{initial velocity + final velocity}}}{2}\\=\dfrac{{{{v}_{1}}+{{v}_{2}}}}{2}\end{array}$

$ \displaystyle {\therefore {{x}_{2}}-{{x}_{1}}=\left( {\dfrac{{{{v}_{1}}+{{v}_{2}}}}{2}} \right)\left( {{{t}_{2}}-{{t}_{1}}} \right)\text{ }…\text{(4)}}$

$ \displaystyle {\text{or }{{x}_{2}}={{x}_{1}}+\left( {\dfrac{{{{v}_{1}}+{{v}_{2}}}}{2}} \right)\left( {{{t}_{2}}-{{t}_{1}}} \right)}$

$ \displaystyle {\because {{v}_{2}}={{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)}$

$ \displaystyle \begin{array}{l}\therefore {{x}_{2}}={{x}_{1}}+\\\left( {\dfrac{{{{v}_{1}}+\left( {{{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)} \right)}}{2}} \right)\left( {{{t}_{2}}-{{t}_{1}}} \right)\end{array}$

$ \displaystyle \begin{array}{l}\Rightarrow {{x}_{2}}={{x}_{1}}+\\{{v}_{1}}\left( {{{t}_{2}}-{{t}_{1}}} \right)+\frac{1}{2}a{{\left( {{{t}_{2}}-{{t}_{1}}} \right)}^{2}}\ldots \text{(5)}\end{array}$

If $ \displaystyle {{x}_{0}},u$ are the displacement and velocity of the object at $ \displaystyle {{t}_{1}}=0$ and x be the displacement of object at t, then using $ \displaystyle {{t}_{1}}=0,\text{ }{{x}_{1}}={{x}_{0}},\text{ }{{v}_{1}}=u,\text{ }{{t}_{2}}=t\text{ and }{{x}_{2}}=x$ in relation (5), we have

$ \displaystyle \begin{array}{l}x={{x}_{0}}+u\left( {t-0} \right)+\dfrac{1}{2}a{{\left( {t-0} \right)}^{2}}\\\Rightarrow x={{x}_{0}}+ut+\dfrac{1}{2}a{{t}^{2}}\text{ }…\text{(6)}\\\Rightarrow x-{{x}_{0}}=ut+\dfrac{1}{2}a{{t}^{2}}\text{ }…\text{(7)}\end{array}$

Using, $ \displaystyle x-{{x}_{0}}=S=$ distance travelled in time t, we have

$ \displaystyle S=ut+\dfrac{1}{2}a{{t}^{2}}\text{ }…\text{(8)}$

The relation (5), (6) and (8) are required position-time relations.

Using relation (6), the position-tie graph for positive and negative accelerations are shown in the image below. These graphs have parabolic shapes.

Positive acceleration:

 

Acceleration

Negative acceleration (Deceleration):

Deceleration

 

(iii) Position-velocity relation

Since,

$ \displaystyle {{v}_{2}}={{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)$

we have

$ \displaystyle \left( {{{t}_{2}}-{{t}_{1}}} \right)=\dfrac{{{{v}_{2}}-{{v}_{1}}}}{a}$

Putting this value in equation (4), we get

$ \displaystyle \begin{array}{*{20}{l}} \begin{array}{l}{{x}_{2}}-{{x}_{1}}=\left( {\frac{{{{v}_{1}}+{{v}_{2}}}}{2}} \right)\left( {\frac{{{{v}_{2}}-{{v}_{1}}}}{a}} \right)\\\Rightarrow {{x}_{2}}-{{x}_{1}}=\frac{{v_{2}^{2}-v_{1}^{2}}}{{2a}}\end{array} \\ {\Rightarrow v_{2}^{2}-v_{1}^{2}=2a({{x}_{2}}-{{x}_{1}})\text{ }…\text{(9)}} \end{array}$

If u and v are the velocities of an object at positions $ \displaystyle {{x}_{0}}\text{ and }x$ respectively, then using $ \displaystyle {{v}_{1}}=u$,

$ \displaystyle {{v}_{2}}=v,\text{ }{{x}_{1}}={{x}_{0}}\text{ and }{{x}_{2}}=x$ in (9), we get

$ \displaystyle {{v}^{2}}-{{u}^{2}}=2a\left( {{{x}_{0}}-x} \right)\text{ }…\text{(10)}$

If $ \displaystyle x-{{x}_{0}}=S$, then

$ \displaystyle {{v}^{2}}={{u}^{2}}+2aS\text{ }…\text{(11)}$

The relations (9), (10) and (11) are the required position-velocity relations.

 

Footer Logo
Briligence brings you a deep learning pattern for science and mathematics which increases your curiosity and clears your concept.
Copyright © 2024 Briligence | All Rights Reserved.
Account
Dark Theme
Light Theme
Share